1998
DOI: 10.1093/oxfordjournals.pcp.a029298
|View full text |Cite
|
Sign up to set email alerts
|

Green Light Drives CO2 Fixation Deep within Leaves

Abstract: Maximal l4 CO 2-fixation in spinach occurs in the middle of the palisade mesophyll [Nishio et al. (1993) Plant Cell 5: 953], however, ninety percent of the blue and red light is attenuated in the upper twenty percent of a spinach leaf [Cui et al. (1991) Plant Cell Environ. 14: 493]. In this report, we showed that green light drives 14 C0 2-fixation deep within spinach leaves compared to red and blue light. Blue light caused fixation mainly in the palisade mesophyll of the leaf, whereas red light drove fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
164
0
8

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(182 citation statements)
references
References 44 publications
10
164
0
8
Order By: Relevance
“…One result identifi ed that when photosynthetic photon fl ux was kept constant, lettuce grown in a combination of red, blue, and green LED light had larger leaf area and higher fresh and dry shoot mass than those grown exclusively under red or blue alone ( Kim et al, 2004a , b ). Their interpretation of this result is that although red and blue light are more effective for promoting photosynthesis, green light might penetrate plant leaves more effi ciently and increase carbon fi xation ( Sun et al, 1998 ;Nishio, 2000 ;Kim et al, 2004b ;Terashima et al, 2009 ). Dry mass of lettuce grown in red-blue (0% yellow light) light was also found to be indistinguishable from that grown in light from white fl uorescent lamps (17% yellow light), a result that differs from Dougher and Bugbee's (2001) .…”
Section: Vegetative Growthmentioning
confidence: 99%
“…One result identifi ed that when photosynthetic photon fl ux was kept constant, lettuce grown in a combination of red, blue, and green LED light had larger leaf area and higher fresh and dry shoot mass than those grown exclusively under red or blue alone ( Kim et al, 2004a , b ). Their interpretation of this result is that although red and blue light are more effective for promoting photosynthesis, green light might penetrate plant leaves more effi ciently and increase carbon fi xation ( Sun et al, 1998 ;Nishio, 2000 ;Kim et al, 2004b ;Terashima et al, 2009 ). Dry mass of lettuce grown in red-blue (0% yellow light) light was also found to be indistinguishable from that grown in light from white fl uorescent lamps (17% yellow light), a result that differs from Dougher and Bugbee's (2001) .…”
Section: Vegetative Growthmentioning
confidence: 99%
“…"%C fixation data are from Sun et al (1998) and the curves are calculated for blue (B), red (R) and green (G) light using the following values for the extinction coefficient : 3636, 2106, 900 m# (mol Chl) −" , respectively.…”
Section: A Test Of Light Capture With Monochromatic Lightmentioning
confidence: 99%
“…become available (Sun, 1996 ;Sun et al, 1998). They provide a robust test of the model, because the absolute response to a variety of lights given to the adaxial surface can be examined for a given leaf.…”
Section: A Test Of Light Capture With Monochromatic Lightmentioning
confidence: 99%
“…Using microscopic light sensors inserted into leaves, it has been shown that light declines rapidly and exponentially within the leaf (Vogelmann et al, 1989 ;Cui et al, 1991 ;Vogelmann & Martin, 1993 ;Vogelmann et al, 1996). In spinach, light within the blue and red parts of the spectrum is absorbed almost completely by the initial palisade cell layers and it is primarily green light that remains for photosynthesis in tissues located deeper within the leaf (Cui et al, 1991 ;Sun et al, 1998). Correspondingly, the distribution of absorbed quanta across the mesophyll tissues is very steep, implying that there could be steep gradients in photosynthetic performance within the leaf (Evans, 1995).…”
Section: mentioning
confidence: 99%
“…Correspondingly, the distribution of absorbed quanta across the mesophyll tissues is very steep, implying that there could be steep gradients in photosynthetic performance within the leaf (Evans, 1995). Measurements of the amount of C fixed by mesophyll layers of spinach (Nishio et al, 1993 ;Sun et al, 1996Sun et al, , 1998 and Vicia (Jeje & *Author for correspondence (tel j1 307 766 6293 ; fax j1 307 766 2851 ; e-mail tvogel!uwyo.edu). Zimmermann, 1983) have shown that the rate of photosynthesis has a Gaussian profile across the leaf.…”
Section: mentioning
confidence: 99%